Zur Erinnerung an den Reichsparteitag 1934 der NSDAP zu Nürnberg... - Unknown photographer... (Wikimedia Commons, 1934)
Carte postale ancienne issue de Wikimedia Commons. Titre: Zur Erinnerung an den Reichsparteitag 1934 der NSDAP zu Nürnberg Postkarte Ansichtskarte Propagandakarte Hakenkreuz Grosses Wappen Harpyie Jungfrauenadler Foto Altstadt Burg Nazi Party propaganda postcard Swastika No known copyright. In commemoration of the Nazi Party Rally 1934 in Nuremberg Picture celebration postcard, advertising card, propaganda card Nazi swastika | Great Coat of Arms of the City of Nuremberg (Harpy) Photo of Nuremberg Castle (Nürnberger Burg) and old town (Altstadt), etc. Nazi propaganda No known copyright
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château